Szkoła w cyfrowym uścisku – z nadzieją nie tylko na igrzyska… - Dylak, Stanisław (Wydawnictwo Naukowe UAM, 2012)
Events which take place in cyberspace complement or even fi ll the day-to-day non-school social life of school-age adolescents. Within cyberspace they have access to limitless amounts of knowledge that assists the solving of any problem. The hours these adolescents spend on the Internet also have an impact on the way in which their cognitive processes and, subsequently, their learning habits develop. Teachers today can take good advantage of the potential existing in the young generation of digital natives by using their online presence to accomplish learning objectives at school.
School in a Cyber-Embrace – With Hope Not Only For Game…
Keywords: digital natives; mass education-mass school; social networking; games for learning